Comparison of Microfat, Nanofat, and Extracellular Matrix/Stromal Vascular Fraction Gel for Skin Rejuvenation: Basic Research and Clinical Applications. (28th January 2021) - Yang, Zhibin; Jin, Shengyang; He, Yu; Zhang, Xinyu; Han, Xuefeng; Li, Facheng
Abstract: Background: Over the past 2 decades, fat grafting has been extensively applied in the field of tissue regeneration. Objectives: The aim of this study was to investigate the therapeutic potential of microfat, nanofat, and extracellular matrix/stromal vascular fraction gel (SVF-gel) in skin rejuvenation. Methods: Microfat was harvested by a cannula with multiple 0.8-mm smooth side holes and processed with a fat stirrer to remove fibers. Nanofat and SVF-gel were prepared according to previously reported methods, and their structure and viability were evaluated. Then, SVF cells from the 3 types of samples were isolated and characterized, and the cell viability was compared. Results: The microstructure of the 3 samples showed distinct differences. The microfat group showed a diameter of 100 to 120.0 μm under the microscope and presented a botryoid shape under calcein acetoxymethyl (calcein-AM)/propidium iodide staining. Scanning electron microscopy analysis showed that the microfat maintained an integral histologic structure. In the nanofat group, no viable adipocytes and no normal histologic structure were observed, but high levels of free lipids were noted. The SVF-gel group showed uniform dispersion of cells with different sizes and parts of the adipose histologic structure. Cell count and culture revealed that the number of viable SVF cells decreased distinctly in the nanofat group compared with the microfat group. In contrast, the number of viable SVF cells in the SVF-gel group increased moderately. Clinical applications with microfat showed marked improvements in skin wrinkles. Conclusions: Microfat can preserve the integrity of the histologic structure and presents the advantages of subcutaneous volumetric restoration and improvement of skin quality in skin rejuvenation compared with the nanofat and SVF-gel. Level of Evidence: 5: